침철석과 자외선 LED를 이용한 아비산염의 광촉매 산화 - 전지훈(Ji-Hun Jeon); 김성희(Seong-Hee Kim); 이상우(Sang-Woo Lee); 김순오(Soon-Oh Kim) (Daehan hwan'gyeong gonghag hoeji, 2017)
Arsenic (As) has been considered as the most toxic one among various hazardous materials and As contamination can be caused naturally and anthropogenically. Major forms of arsenic in groundwater are arsenite [(As(III)] and/or arsenate [(As(V)], depending on redox condition: arsenite and arsenate are predominant in reduced and oxidized environments, respectively. Because arsenite is much more toxic and mobile than arsenate, there have been a number of studies on the reduction of its toxicity through oxidation of As(III) to As(V). This study was initiated to develop photocatalytic oxidation process for treatment of groundwater contaminated with arsenite. The performance of two types of light sources (UV lamp and UV LED) was compared and the feasibility of goethite as a photocatalyst was evaluated. The highest removal efficiency of the process was achieved at a goethite dose of 0.05 g/L. Based on the comparison of oxidation efficiencies of arsenite between two light sources, the apparent performance of UV LED was inferior to that of UV lamp. However, when the results were appraised on the basis of their emitting UV irradiation, the higher performance was achieved by UV LED than by UV lamp. This study demonstrates that environmentally friendly process of goethite-catalytic photo-oxidation without any addition of foreign catalyst is feasible for the reduction of arsenite in groundwater containing naturally-occurring goethite. In addition, this study confirms that UV LED can be used in the photo-oxidation of arsenite as an alternative light source of UV lamp to remedy the drawbacks of UV lamp, such as long stabilization time, high electrical power consumption, short lifespan, and high heat output requiring large cooling facilities. 비소는 다양한 유해물질들 중 독성이 가장 크다고 알려져 있으며, 자연발생 또는 인간의 활동으로부터 비소오염이야기될 수 있다. 지하수 내 비소는 환원 환경에서 아비산염, 산화 환경에서 비산염 형태로 존재한다. 아비산염은 비산염보다 독성이 강하고 이동성이 더 크기 때문에 아비산염을 비산염으로 산화시켜 독성을 저감시키기 위한 연구가 많은 관심을 받고 있다. 본 연구에서는 비소로 오염된 지하수로부터 독성이 높은 아비산염을 독성이 낮은 비산염으로 산화시키기 위하여 자외선램프 및 자외선 LED 광원과 침철석 촉매를 이용한 광촉매 산화 공정에 대하여 연구하였다. 광산화 실험에서 광촉매로 사용된 침철석의 투여량이 0.05 g/L일 때 가장 높은 광산화 효율을 나타났다. 또한 광원의 파장별 겉보기 광산화 효율을 비교한 결과, 자외선램프가 자외선 LED에 비하여 아비산염의 산화 효율이 더 높은 것으로 나타났다. 하지만, 자외선 방사량을 기준으로 보정하면, 자외선 LED가 자외선램프보다 광산화 효율이 더 높은 것으로 평가되었다. 본 연구를 통해 침철석 광물이 존재하는 지하수 환경에서 외부로부터 다른 광촉매를 투여하지 않고 친환경적인 광산화 공정을 이용하여 비소의 독성 저감이 가능하다는 것을 알 수 있었다. 또한, 공정 또한 자외선 LED가 자외선램프의 단점을 보완할 수 있는 대체 광원으로 광산화 공정에 활용 가능하다는 것을 확인하였다.